APLIKASI SISTEM PENGENDALI ENERGI LISTRIK MENGGUNAKAN RASPBERRYPI PADA SMART BUILDING - Masnur, Masnur (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
Electrical energy is a very important requirement that must be met for human needs. The savings in electricity use have an impact on the preservation of nature apart from the usage costs incurred. Waste of electricity usage usually occurs due to negligence of users such as not turning off electrical equipment or forgetting to leave the room. Then the system